The role of rapid on site evaluation on touch imprint cytology and brushing during conventional bronchoscopy. Issue 7 (12th April 2021) - Botticella, Maria Antonietta; De Summa, Simona; Cisternino, Luigi; Tommasi, Stefania; Pastena, Maria Irene; Schirosi, Laura; Mangia, Anita; Mele, Fabio; Lozupone, Antonietta; Scattone, Anna; Siciliano, Michele; Sozio, Rosa; et al.
Abstract: Background: The increase in immunohistochemical and molecular predictive tests in lung cancer requires new strategies for managing small samples taken during bronchoscopic procedures. The value of Rapid On Site Evaluation (ROSE) during conventional bronchoscopic procedures on endobronchial neoplasms in optimizing small biopsies and cytologlogical tissue specimens for diagnostic testing, and ancillary studies was evaluated. Method: ROSE on touch imprint cytology (TIC) and brushing was performed on 690 consecutive cases of patients undergoing biopsies, using fiber optic bronchoscopy. Immunohistochemical assay for PD‐L1, ALK, and ROS1 and molecular testing, via next generation technique for EGFR, KRAS, and BRAF, were performed. Results: The concordance between ROSE and final diagnoses was almost perfect for brushing (sensitivity: 0.84; specificity: 0.96), and less so for touch preparations (sensitivity: 0.77; specificity: 0.89). Immunohistochemical assay for PD‐L1 was evaluated on 256 bioptic cases with only six unsuitable samples. Material available for immunohistochemistry for ALK was sufficient in 151 biopsies with no inadequate cases. ROS1 was evaluated in 132 biopsies, with only two unsuitable samples. Molecular analysis was performed on 128 biopsies, 29 TIC, and 17 brushing. Out of these, only ten were considered to be unsuitable. Conclusions: ROSE is an effective procedure for monitoring the quality and quantity of material taken during conventional bronchoscopic procedures for evaluating the suitability of small samples that must undergo immunohistochemical and molecular assay.